2008
DOI: 10.1038/sj.bjc.6604124
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the reduced expression of G protein gamma 7 (GNG7) in oesophageal cancer

Abstract: We previously cloned human G protein gamma 7 (GNG7) and demonstrated that it was downregulated in gastrointestinal cancer. The significance of GNG7 expression in oesophageal cancer is unknown. TaqMan quantitative real-time PCR was performed to determine the clinical significance of GNG7 expression in 55 cases of oesophageal cancer. Furthermore, GNG7-transfected oesophageal cancer cells were analysed in laboratory studies at genomic and epigenetic levels. Twenty-seven patients with low GNG7 expression showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 19 publications
7
48
1
Order By: Relevance
“…Interestingly, in patients with no TMEM127 mutation but with 2q11 LOH, TMEM127 mRNA levels were also decreased by 35%, thus showing that 2q11 LOH itself had a dosage effect. Such a correlation has already been reported for many other genes, such as 19p13 LOH and GNG7 expression in esophageal cancer (14) or 3p14 LOH and FHIT expression in breast cancer (15).…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, in patients with no TMEM127 mutation but with 2q11 LOH, TMEM127 mRNA levels were also decreased by 35%, thus showing that 2q11 LOH itself had a dosage effect. Such a correlation has already been reported for many other genes, such as 19p13 LOH and GNG7 expression in esophageal cancer (14) or 3p14 LOH and FHIT expression in breast cancer (15).…”
Section: Discussionmentioning
confidence: 74%
“…MiRNA expression profiles have been frequently reported to be correlated with the etiology, classification, progression, and prognosis of multiple human cancers including esophageal cancer (8, 13-17). However, whether genetic variants of miRNA-related genes have an influence on esophageal cancer risk has largely remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The observed reductions in levels of Ga olf , Gb 1 , and Gb 2 in these different models provide further evidence of cell-type-specific post-translational mechanisms where Gg subunits stabilize partner subunits of the heterotrimeric G protein. This is interesting in the context of esophageal cancer, where levels of Gg 7 are reduced (Ohta et al, 2008), suggesting that the effects again go beyond a simple signaling phenotype. Furthermore, it was reported that, in wild-type mice, there is a 4-fold molar excess of Gg 2 yet equimolar amounts of Gg 3 compared with Gg 7 in the striatum, and surprisingly, a 40% increase in Gg 3 and slight decrease in Gg 2 was noted upon loss of Gg 7 , a possible reflection of an adaptive mechanism in which Ga i/o and Ga olf signaling are involved in a common neurologic pathway (Schwindinger et al, 2010).…”
mentioning
confidence: 98%